Content creator performance measurement system design using rapid application development - Eugenius Kau Suni (Jurnal Mantik, 2024)
This research aims to analyze the performance of content creators, employing the Rapid Application Development (RAD) methodology with stages including requirement planning, user design, construction, and cutover. The results of this study demonstrate the necessity of a database and information system for measuring the performance of content creators to analyze competitors and enhance competitiveness. By utilizing RAD methodology, the research emphasizes the importance of iterative development and user involvement in crafting a robust system tailored to the evolving needs of content analysis and strategic planning. Consequently, the findings underscore the significance of data-driven approaches in optimizing content strategies and fostering competitiveness in the digital landscape. The practical implications of this application lie in its capability to manage content creator data and monitor content statistics effectively. By serving as a centralized database and monitoring system, the application streamlines collecting, organizing, and analyzing data related to content creators and their performance metrics